The limited memory of value following value directed encoding. - Filiz, Gizem; Dobbins, Ian G. (Memory & Cognition, 2024)
Items associated with higher values during encoding are later recognized and recalled better than are lower valued items. During recall paradigms, these value directed encoding (VDE) effects heavily depend upon learned strategies acquired during repeated testing with earnings feedback. However, because VDE effects also occur in single test recognition designs, precluding such learning, it has been suggested that high value may automatically induce good encoding. We tested this by manipulating encoding instructions (Experiments 1a and 1b) and manipulating concurrent levels of processing (LOP) requirements during encoding (Experiment 2a and 2b). Two main findings emerged. First, subject initiated strategies played a dominant role in VDE effects with little evidence for automaticity. This was demonstrated in Experiment 1 by a more than three-fold increase in the VDE recognition effect when instructions specifically encouraged selective elaboration of high-value items. It was also shown by the complete elimination of VDE recognition effects in Experiment 2 when LOP tasks were concurrently performed during encoding. Critically, the blocking of VDE effects occurred even though a catch trial procedure verified that value was being processed during encoding and remained even when subjects had unlimited time to process the materials during encoding. Second, the data showed, for the first time, that when subjects attempted to specify the value of recognized items, they heavily depended upon a recognition heuristic in which increases in recognition strength, even when nondiagnostic, were inferred to reflect high encoding value. The tendency for subjects to conflate recognition strength and value may have important implications for behavioral economics.